Challenges in Translating Idioms in Audiovisual Translation - Gaman, Alexander Paruda; Darta, Deta Maria Sri (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
In the world of audiovisual translation, subtitles are often used to help audiences understand foreign language content, such as English films for Indonesian audiences. However, subtitle translation is not a simple job, especially when dealing with complex linguistic elements such as idioms. Thus, this research aims to analyze how idioms in the movie “Madagascar” were translated into subtitles. The qualitative descriptive method is used for this research. The analysis reveals that the movie contains 79 idioms. Most of the idioms were translated using Baker’s four idiom translation strategies. However, there are several cases where an idiom was not translated correctly. Thus, it resulted in semantic loss and led to a failure in the audience’s understanding. Through this research, it is evident that linguistic, contextual, and cultural precision are critical requirements for translators.